Active Methodologies in Higher Education: Perception and Opinion as Evaluated by Professors and Their Students in the Teaching-Learning Process - Crisol-Moya, Emilio; Romero-López, María Asunción; Caurcel-Cara, María Jesús (Frontiers in Psychology, 2020)
The goal of this study is both to determine the opinion that professors and students at the university have of active methodologies and to describe the perception and opinion of the modes of organization, methodological focuses, and evaluation systems that define the teaching-learning process. On surveying the professors and the students in their classes, we found significant differences in 32 of the 92 variables in common. The content of these results shows that professors and students are believe they are making progress toward a learning-centered model, that implementation of active methodologies implies new functions in their teaching practice.